NEW VIEWS ON CLINICAL AND LABORATORY ASPECTS OF ROTAVIRUS INFECTION - Umarova T. A.; Kudratova Z. E.; Abduazizova Z. (Web of Journals Publishing, 2024)
Rotavirus infection is caused by an RNA virus having 5 serogroups (A-E) with a much larger number of serotypes. It is transmitted by the contact route. Causes watery diarrhea, often with vomiting and fever, secondary to lactase deficiency.
Keywords: Diarrhea, anthroponotic viral acute infectious, fecal-oral transmission mechanism.